Propuesta de diseño de política pública cultural, para un festival nacional de artes en Ecuador - Carvallo Iñiguez, Kathy Vanessa (2024)
In Ecuador, the organization of the International Festival of Living Arts Loja (FIAVL) emphasizes the importance of establishing cultural ties from various parts of the world. However, the absence of a national festival of living arts raises fundamental questions about how indigenous cultural and artistic expressions are promoted and disseminated. Although the budget allocation to the Ministry of Culture and Heritage (MCYP) significantly reflects the government's commitment to culture, the current prioritization of an international festival of living arts over a national festival has significant consequences for the cultural sector. This can be observed in a lack of job generation in this sector and the allocation of a percentage of resources earmarked for culture to foreign participants who are part of the International Festival of Living Arts. This research aims to design a proposal for a cultural public policy to promote and preserve local culture through a national arts festival. It is based on documentary information, along with a diagnosis of the current cultural public policy. The main results derived from this study indicate that the live and performing arts sector is the most sought- after in projects, with this group of actors being the second most represented. Limitations are evident, such as the lack of attention to marginalized areas and a high level of unemployment in the cultural sector. The decrease in the production of works in live and performing arts in 2023 highlights the need for additional incentives to boost artistic creation, possibly through support for national arts festivals or programs aimed at fostering artistic production and the participation of local artists.